Demographic Characteristics of 1082 Positive Cases of COVID-19 Patients: Experience at National Referral Laboratory of Bangladesh (Bangladesh Journal of Infectious Diseases, 2020)
Background: COVID-19 has now become a pandemic.Objective: The aim of this study was to characterize the demographic features with infection rate of SARS-CoV-2 in 4/5 divisions of Bangladesh.Methodology: This cross-sectional study was conducted at National institute of Laboratory Medicine and Referral Center, Dhaka, Bangladesh from 15th April to 30th April, 2020. It was performed RT-PCR for 2462 cases within the time frame and 1082 samples were positive for SARS CoV-2. Patient demographic characteristics including age, gender, occupation and blood group was investigated.Results: The mean age of positive cases was 40.2 ± 15.33 years, 426 (39%) cases were 25-39 years of age. The majority of cases were male (71%) and the predominant blood group was B positive (37%).Conclusions: In conclusion male gender, younger age and blood group B positive are more commonly suffering from COVID-19 infection.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S22-S26